Methods and instrumentation for the biomechanical analysis of slalom water skiing. (June 2014) - Bray-Miners, Jordan; Runciman, R John; Groendyk, Nathaniel
Many highly dynamic sporting activities are now quantitatively analyzed to optimize athletic performance and provide information required for equipment optimization. Water skiing (with its challenging environmental conditions) has to date received only minimal attention in this area. The objective of this study was to create an instrumentation system suitable for analyzing the biomechanics of slalom water skiing. An instrumentation system and methodology were designed and implemented to collect quantitative data for slalom water skiing at the advanced level. The chosen performance parameters of interest for slalom water skiing turns were skier velocity, ski acceleration, ski deceleration, ski roll and rope load. Four sensors were used to collect data to calculate the parameters of interest: a boat-based global positioning sensor unit, a skier-mounted global positioning system unit, axial load transducer mounted in the tow rope and a ski-mounted inertial measurement unit. A novel custom-fabricated and programmed wireless communication system was incorporated in the study to allow rapid data communication and acquisition. Results indicate that the instrumentation system developed for this study was successful in providing the data deemed necessary for the biomechanical analysis of slalom water skiing. The data provide a unique look into the complex three-dimensional biomechanics of slalom water skiing. This same quantitative data would be suitable for advanced ski equipment design, injury prevention and high-level athlete coaching of slalom skiers. It is also expected that the equipment developed for this study would be suitable for use at novice and intermediate levels of water skiing and with minor alternations could be applied to the analysis of other open-water sports.